Mānasa-pravacana - Upādhyāya, Rāmakiṅkara (Biralā Akādamī āpha Ārṭa eṇḍa Kalcara, 1982)
Discourses on Tulasīdāsa's Rāmacaritamānasa, 17th century Awadhi extended narrative poem on the life and exploits of Rāma, Hindu deity.